In vitro virucidal efficacy of a dry steam disinfection system against Human Coronavirus, Human Influenza Virus, and Echovirus. Issue 12 (2nd December 2021) - Marchesi, Isabella; Sala, Arianna; Frezza, Giuseppina; Paduano, Stefania; Turchi, Sara; Bargellini, Annalisa; Borella, Paola; Cermelli, Claudio
Abstract: This in vitro study was aimed to assess the efficacy of dry steam in inactivating Human Coronavirus OC43 (HCoV-OC43) as surrogate of SARS-CoV-2, Human Influenza Virus A/H1N1/WSN/33 and Echovirus 7 on stainless steel, polypropylene, and cotton. The virus models were chosen on the basis of their transmission route and environmental resistance. Tests were carried out under a laminar flow cabinet, where two panels of each material were contaminated with a viral suspension. The inocula were left to dry and then the virus on untreated panel (control) was collected by swabbing in order to determine the initial titer. The other panel was treated using a professional vacuum cleaner equipped with a dry steam generator. Dry steam is generated in a boiler where tap water is heated up to 155 °C at 5.5 bar pressure and then during the passage along the flexible hose the temperature decreases to a value between 100 °C and 110 °C at the output. The dry steam was applied for four sec with a window wiper on metal and plastic panels or a brush covered by a microfiber cap on cotton, simulating the steam application during routine cleaning. After the treatment, infectious virus possibly remained on the surface was collected following the same swabbing procedure applied for controls. HCoV-OC43 and Echovirus 7 were titrated by end-point method on HCT-8 line cells and Vero cells, respectively, while Human Influenza Virus was quantified by plaque reduction assay on MDCK cells. Dry steam resulted effective against the three viruses on all tested materials, achieving a mean Log10 reduction factor ≥4 in viral titer of treated samples compared with controls according to UNI EN 14476:2019. Thus, dry steam may be proposed as an ease to use, effective, fast, and nontoxic alternative to chemicals for surface disinfection without damaging materials. Therefore, this device could be employed not only in healthcare facilities but also in occupational, domestic, and community settings, with advantages for environment and human health.